ssRNA Virus and Host Lipid Rearrangements: Is There a Role for Lipid Droplets in SARS-CoV-2 Infection? - Pagliari, Francesca; Marafioti, Maria Grazia; Genard, Geraldine; Candeloro, Patrizio; Viglietto, Giuseppe; Seco, Joao; Tirinato, Luca (Frontiers in Molecular Biosciences, 2020)
Since its appearance, SARS-CoV-2 has immediately alarmed the World Health Organization for its very high contagiousness and the complexity of patient clinical profiles. The worldwide scientific community is today gathered in a massive effort in order to develop safe vaccines and effective therapies in the shortest possible time. Every day new pieces of SARS-CoV-2 infective puzzle are disclosed. Based on knowledge gained with other related coronaviruses and, more in general, on ssRNA viruses, we highlight underexplored molecular routes in which lipids and lipid droplets (LDs) might serve essential functions in viral infections. In fact, both lipid homeostasis and the pathways connected to lipids seem to be fundamental in all phases of the coronavirus infection. This review aims at describing potential roles for lipid and LDs in host-virus interactions and suggesting LDs as new and central cellular organelles to be investigated as potential targets against SARS-CoV-2 infection.